Navigating the entrepreneurial knowledge and competence among vocational students: the role of economics education - Suparno, Suparno; Fidhyallah, Nadya Fadillah; Aljero, Rafi Kurniaji; Adha, Maulana Amirul; Narmaditya, Bagus Shandy; Othman, Norashida (Journal of Education and Learning (EduLearn), 2025)
Vocational education in Indonesia is emphasized not only to develop competent workers but also to foster innovative and independent entrepreneurs, aligning with government policies to create more young entrepreneurs amid global competition and evolving job market demands. This study aims to investigating the influence between economic education and entrepreneurial competence (ECOMP), with entrepreneurial knowledge (EK) as a mediator. This study employs a quantitative approach, using surveys conducted at vocational high schools in Jakarta. A sample of 247 students was collected through convenience sampling, and data was processed using structural equation modeling (SEM) with Amos 25. The study found that economics education (EC) significantly enhances EK and competence among vocational high school students, both directly and indirectly. By developing a strong understanding of economic and business concepts, students are better equipped to succeed in the business activities. The findings emphasize the importance of improving EC with a focus on practical applications to help students acquire the essential skills required to achieve success as entrepreneurs.